2012
DOI: 10.1371/journal.pone.0033479
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Taxonomic Groupings Mask Evolutionary History: A Molecular Phylogeny and New Classification of the Chromodorid Nudibranchs

Abstract: Chromodorid nudibranchs (16 genera, 300+ species) are beautiful, brightly colored sea slugs found primarily in tropical coral reef habitats and subtropical coastal waters. The chromodorids are the most speciose family of opisthobranchs and one of the most diverse heterobranch clades. Chromodorids have the potential to be a model group with which to study diversification, color pattern evolution, are important source organisms in natural products chemistry and represent a stunning and widely compelling example … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
107
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(118 citation statements)
references
References 55 publications
7
107
0
Order By: Relevance
“…Subsequently, multilocus analyses appeared utilizing a variety of nuclear and mitochondrial markers to unravel phylogenetic relationships within Opisthobranchia and subgroups (e.g. Wägele et al 2003;Grande et al 2004a, b;Vonnemann et al 2005;KlussmannKolb and Dinapoli 2006;Händeler and Wägele 2007;Händeler et al 2009;Malaquias et al 2009;Klussmann-Kolb 2010a, b, 2011;Maeda et al 2010;Pola and Gosliner 2010;Moore and Gosliner 2011;Johnson and Gosliner 2012;Pola et al 2012;Corse et al 2013;Carmona et al 2013, and many more) (Fig. 3a, b) or phylogenetic relationships of opisthobranch taxa within Euthyneura (Grande et al 2004b;Klussmann-Kolb et al 2008;Jörger et al 2010;Göbbeler and Klussmann-Kolb 2011;Dayrat et al 2011;Schrödl et al 2011a; (Fig.…”
Section: Molecular Approachesmentioning
confidence: 99%
“…Subsequently, multilocus analyses appeared utilizing a variety of nuclear and mitochondrial markers to unravel phylogenetic relationships within Opisthobranchia and subgroups (e.g. Wägele et al 2003;Grande et al 2004a, b;Vonnemann et al 2005;KlussmannKolb and Dinapoli 2006;Händeler and Wägele 2007;Händeler et al 2009;Malaquias et al 2009;Klussmann-Kolb 2010a, b, 2011;Maeda et al 2010;Pola and Gosliner 2010;Moore and Gosliner 2011;Johnson and Gosliner 2012;Pola et al 2012;Corse et al 2013;Carmona et al 2013, and many more) (Fig. 3a, b) or phylogenetic relationships of opisthobranch taxa within Euthyneura (Grande et al 2004b;Klussmann-Kolb et al 2008;Jörger et al 2010;Göbbeler and Klussmann-Kolb 2011;Dayrat et al 2011;Schrödl et al 2011a; (Fig.…”
Section: Molecular Approachesmentioning
confidence: 99%
“…However, Carmona et al (2013) found genetic differences between these two species (minimum uncorrected p-distance = 7.3 % for COI between L. nodosa and L. confusa, see Table 2 of that contribution). Recent studies supported by molecular phylogenies are starting to separate taxa with ecological or geographical differences (Claremont et al 2011;Johnson and Gosliner 2012). Clearly, both species have distinct geographical patterns (Atlantic-Mediterranean for L. nodosa and Pacific for L. confusa).…”
Section: Systematics Nudibranchia Cuvier 1817 Cladobranchia Willan Anmentioning
confidence: 99%
“…Marcus, 1967; Glossodoris Ehrenberg, 1831 and Chromodoris Alder and Hancock, 1855, both as part of the provisional genus 'Felimida' Ev. Marcus, 1971;and Risbecia Odhner, 1934, synonymized by Johnson and Gosliner (2012) with Hypselodoris. Ortea's et al (1996) review, however, did not include in this group other Atlantic species clearly belonging to the blue chromatic group, such as Felimare zebra (Heilprin, 1889) from Bermuda.…”
Section: Introductionmentioning
confidence: 99%
“…The Felimare genus was re-erected by Johnson and Gosliner (2012). According to these authors, Felimare should include all the eastern Pacific, Atlantic and Mediterranean species previously attributed to Hypselodoris as well as two species of Mexichromis (one from the eastern Pacific and one from the Caribbean).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation